Acceleration of 3D crack propagation simulation by the utilization of fast BEM-techniques - Weber, Wilhelm; Kolk, Karsten; Kuhn, Günther (Engineering Analysis With Boundary Elements, 2009)
For the acceleration of the 3D simulation of fatigue crack propagation fast BEM techniques are combined in the present paper. The so-called dual BEM is utilized to separate the coincident crack surfaces. In the present context, the relevant boundary integral equations are evaluated in the framework of a collocation procedure. For the reduction of the numerical complexity of the stress analysis fast BEM techniques are applied. The domain is decomposed in order to obtain a band-structured system matrix. The crack is modeled in terms of the dual discontinuity method. Therewith, the relevant boundary of the domain is reduced by one crack surface. Finally, the adaptive cross approximation, an algebraic matrix compression technique, is utilized to compress the system matrix. The efficiency of this procedure is shown on complex industrial applications. © 2009 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2009.tech.FT.FT-TM.bem
Keywords: 3D dual BEM; Adaptive cross approximation (ACA); Domain decomposition; Dual discontinuity method (DDM)